Marketing of Eucalyptus Woog with Special Reference to Punjab - Sagar, S. R. (Indian Forester, 1983)
Eucalyptus hybrid (Mysore gum) proved capable of adapting itself to a wide variety of ecological zones. The growth both in height and diameter is seen higher in Agriculture farms thun under forest conditions. The wood is found suitable for end-uses viz. pulp manuracture, fuelwood, building material, poles, packing cases etc, This species made its way to Agriculture presumably during 2nd Five Year Plan period. Today it is being grown by farmers all over India. This study highlights the market prices of different end-use wise of Eucalyptus wood in Punjab during the year 1981, 1982 and 1983 and examines various aspect of utilization. It is suggested to set up forest product price commission to fix thesh-hold prices of different enduse products in order to save the farmers from vagaries of the markets.